Peningkatan Kapasitas Digital Marketing Bagi UMKM Melalui Pelatihan Media Sosial Dan Marketplace Lokal - Dicky Surya Putra Pradana; I Made Bagus Dwiarta; Bisma Arianto; Yuli Kurnia Firdausia; Rovilla El Maghrviroh (Ekobis Abdimas, 2025)
This community service activity aims to increase the capacity of Micro, Small, and Medium Enterprises (MSMEs) in the field of digital marketing through social media training and utilization of local marketplaces. In the digital era, digital marketing skills are very important so that MSMEs can survive and compete. This activity was carried out in Taman village, Taman Sidoarjo District in the form of intensive training that includes theory and direct practice. The results of the activity showed an increase in participants' understanding and skills in managing social media and utilizing the marketplace as a means of sales.